Grit, Persepsi Dukungan Organisasi, Karakteristik Pekerjaan dan Pengaruhnya terhadap Kualitas Hidup - Laili Irawati; Rostiana Rostiana (Jurnal Manajemen dan Organisasi, 2021)
Working as an IT employee who must meet Service Level Agreement (SLA) to customers means having to do the best for customers even though they are no longer in working hours. This way of working will ultimately affect the quality of life. Therefore, this study aims to determine which of the grit, perceived organizational support and job characteristics will affect the quality of life of IT employees. This research was conducted using a non-probability sampling technique, namely employees who work in the IT department who have service standards to customers in carrying out their work. Research data collection was carried out twice with a data collection time of 1 to 3 weeks between the first study and the second study. The number of participants in the first study was 199 people and the second study was 128 people. The results showed that job characteristics became the dominant factor affecting the quality of life of IT employees. Meanwhile, grit and perceived organizational support do not affect the quality of life of IT employees. With about 70 percent of the study participants being male, it is understandable if work becomes an important part of a person's life so that even though he works with high work demands he still feels he has a good quality of life.